Cytogenetic characterization of Diachasmimorpha longicaudata (Hymenoptera: Braconidae), a parasitoid wasp used as a biological control agent - Carabajal Paladino, Leonale Suzel; Papeschi, Alba Graciela; Lanzavecchia, Silvia Beatriz; Cladera, Jorge Luis; Bressa, María José (Czech Academy of Sciences, 2021)
Diachasmimorpha longicaudata (Hymenoptera: Braconidae) is a parasitoid wasp widely used in the biological control of fruit flies. In this paper, we present a detailed analysis of the karyotype of this species based on the results of classical and molecular cytogenetic techniques. The cytogenetic analysis confirmed the male and female chromosome numbers previously reported (n = 20, 2n = 40). The entire short arm of most chromosomes is made up of a large constitutive heterochromatic segment. The high heterochromatin content differentiates D. longicaudata from other braconid species. Fluorescence in situ hybridization (FISH) using autologous 18S rDNA probes revealed six clusters of rDNA, i.e. six nucleolar organizer regions (NORs), in the heterochromatic short arms of different chromosomes in the haploid male karyotype. This number is exceptionally high for Hymenoptera, which usually have two NORs in the diploid complement. It is noteworthy that these rDNA-FISH experiments represent the first use of this technique on a braconid species using autologous probes. Since Ag-NOR-bands were coincident with C-positive bands on metaphase chromosomes, it was not possible to identify active nucleoli. The physical characteristics of the D. longicaudata karyotype, especially the content and distribution of heterochromatin and the number and location of rDNA clusters, contribute to a better understanding of the structure and organization of braconid chromosomes and provide a basis for genomic and evolutionary studies.